Peculiarities of State Regulation for the Development of Local Self-Governance - T. H. Bondaruk (Статистика України, 2016)
Theoretical and methodological framework for regulation of the development of local self-governance is extended, with outlining the ways to strengthen its contribution as a factor promoting social and economic development of a country. It is demonstrated that the regulatory framework at local level covers all the governance areas, including regulation of local self-governance. The essential meaning of the regulatory policy at local level is defined as an area of State policy, focused on regulation of legal relations between regulatory bodies, between the entities charged with regulatory functions and the entities that are subject to regulation; it includes regulation of local self-governance, territorial communities and business entities for rational use of local resources and essential growth in the living standards of the population.